2015
DOI: 10.1007/s00270-015-1077-4
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory-Induced Haemodynamic Changes: A Contributing Factor to IVC Filter Penetration

Abstract: Caval morphology and hemodynamics are clearly affected by Valsalva maneuvers. A physiological reduction of IVC cross-sectional area is associated with higher risk of filter penetration, despite short dwell times. Physiologic data should be used to improve future filter designs to remain safely implanted over longer dwell times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 20 publications
3
28
1
Order By: Relevance
“…We read with great interest the study published by Laborda et al about the relationship between inferior vena cava size and pressure, and filter migration or penetration [1]. We agree completely with their findings concerning the effects of ventilation and valsalva maneuvers on the hemodynamics and anatomy of the inferior vena cava (IVC).…”
supporting
confidence: 61%
“…We read with great interest the study published by Laborda et al about the relationship between inferior vena cava size and pressure, and filter migration or penetration [1]. We agree completely with their findings concerning the effects of ventilation and valsalva maneuvers on the hemodynamics and anatomy of the inferior vena cava (IVC).…”
supporting
confidence: 61%
“…5,6 Changes in IVC pressure may play a role in acute filter migration. 2,7,8 Prone positioning for spinal surgery can cause sudden changes in IVC size and pressure 6,9-13 and may be a contributing factor to the migration of a newly inserted IVC filter. This factor may be even more important with the use of more recent devices (e.g., flexible retrievable filters).…”
Section: Résumémentioning
confidence: 99%
“…However, there are other physiological situations such as the Valsalva maneuver or the influence of diaphragmatic motion on vena cava shape and size that could cause penetration . Laborda et al demonstrated that filter penetration could be related with IVC cross‐sectional area decrease during Valsalva. We have only analyzed neutral breathing; futures studies should be done in order to check if the radial force produced by Valsalva maneuver could produce a major penetration of the struts.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the filter was deployed in the cava by radially removing the previous applied force and allowing the outer surface of the anchor to come into contact with the inner surface of the cava; see Figure . The influence of diaphragmatic motion on vena cava shape and size in the context of neutral breathing and Valsalva has not been considered …”
Section: Computational Modeling Of the Deployment Of The Filtermentioning
confidence: 99%